Heisteria austroecuadorica (Erythropalaceae): A new species from southeastern Ecuador - Cornejo, Xavier; Homeier, Jürgen; Ulloa Ulloa, Carmen (Phytotaxa, 2023)
Heisteria austroecuadorica, a new species of Erythropalaceae from the conserved evergreen montane forest at the San Francisco reserve, in southeastern Ecuador, is here described and illustrated. It is characterized by the flowers with 10 stamens, and relatively large fruits, with the apex conspicuously depressed, and the calyx not covering the base of the fruits. Heisteria austroecuadorica is assessed provisionally as Endangered.